2009
DOI: 10.1021/nn901161w
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Nanoparticle Necklaces Network Showing Single-Electron Switching at Room Temperature and Biogating Current by Living Microorganisms

Abstract: A network of one-dimensional (1D) Au nanoparticle necklaces is synthesized and shown to exhibit electronic switching, that is, gating, by the metabolic activity of yeast cells deposited on the structure. Without the cells, the network exhibits the Coulomb blockade effect at room temperature with a sharp threshold voltage, V(T) of approximately 0.45 V, which corresponds to a switching energy of approximately 20 kT. Although the enhancement in V(T) from approximately 70 mV for a single (10 nm) Au particle to >1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 40 publications
4
58
0
Order By: Relevance
“…Their shapes may be spheres, discs or rods. The study of nanofluids is an important branch of nanotechnology, since it has potential applications in transportation and electronics cooling (Buongiorno et al, 2009;Eastman, Choi, Li, Yu, & Thompson, 2001;Godson, Raja, Mohan Lal, & Wongwises, 2010;Shalkevich, Shalkevich, & Bürgi, 2010;Wang & Mujumdar, 2007;Wu et al, 2010), biomedicine (Ai et al, 2005;Grainger & Castner, 2008;Ma & Liu, 2007;Nasongkla et al, 2006;Xu, Li, Li, Feng, & Gao, 2009), oil drilling (Ju, Fan, & Ma, 2006), nano-structure fabrication (Ai et al, 2005;Choi & Alivisatos, 2010;DeVries et al, 2007;Kane, Inan, & Saraf, 2010;Nasongkla et al, 2006;Rao et al, 2009;Tam et al, 2010) and nanocomposites (Rao & Chen, 2008;Guo, Han, Li, & Zhao, 2010;Lu, Liu, & Lee, 2005). Its fundamental science spans colloidal science, surface chemistry, fluid mechanics and materials science.…”
Section: Introductionmentioning
confidence: 99%
“…Their shapes may be spheres, discs or rods. The study of nanofluids is an important branch of nanotechnology, since it has potential applications in transportation and electronics cooling (Buongiorno et al, 2009;Eastman, Choi, Li, Yu, & Thompson, 2001;Godson, Raja, Mohan Lal, & Wongwises, 2010;Shalkevich, Shalkevich, & Bürgi, 2010;Wang & Mujumdar, 2007;Wu et al, 2010), biomedicine (Ai et al, 2005;Grainger & Castner, 2008;Ma & Liu, 2007;Nasongkla et al, 2006;Xu, Li, Li, Feng, & Gao, 2009), oil drilling (Ju, Fan, & Ma, 2006), nano-structure fabrication (Ai et al, 2005;Choi & Alivisatos, 2010;DeVries et al, 2007;Kane, Inan, & Saraf, 2010;Nasongkla et al, 2006;Rao et al, 2009;Tam et al, 2010) and nanocomposites (Rao & Chen, 2008;Guo, Han, Li, & Zhao, 2010;Lu, Liu, & Lee, 2005). Its fundamental science spans colloidal science, surface chemistry, fluid mechanics and materials science.…”
Section: Introductionmentioning
confidence: 99%
“…The use of emerging methods of EHD printing, such as combinations with AFM-capillaries for closed-loop nanoscale nozzle-surface separation 37,38 , would greatly improve the resolution we show here for continuous printing. This could be used to directly print far denser networks of nanoparticles, opening a route for the use of additive nanomanufacturing to create singleelectron device circuitry 5 , sensors 2 , and nanoplasmonic devices 3 . Nanoparticles can also be positioned through this process to enable the assembly of other components, such as the positioning of optoelectronic components 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Additive manufacturing such as three-dimensional (3D) printing technologies have served to fill this gap for lower volume manufacturing of late, but such techniques have not made it into the nanoscale domain. Burgeoning methods of additive nanomanufacturing offer a potential solution to this problem, by enabling the top-down integration of existing devices with nanomaterials [1][2][3][4][5][6] , whose properties have demonstrable applications in novel areas of biosensing 4 , single-electron transport 5 , quantum phenomena 6 , and more. These materials can be made to self-assemble into desired configurations via many driving forces, from electrophoresis [7][8][9][10] , DNA-linkages 11,12 and geometrical interactions [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…One example where ANM can enable new structures is the assembly of nanoparticles into functional devices. It has been shown that a wire of gold nanoparticles can be used as single electron transistors 174 but it is currently almost impossible to massmanufacture such structures. Probe-based pick-and-place ANM can accurately position nanoparticles in the desired configuration making such devices possible in the future ( See FIG.…”
Section: Discussionmentioning
confidence: 99%